Pemberdayaan Warga Desa Pulau Semambu melalui Diversifikasi Produk Olahan Ikan - Sherly Ridhowati; Siti Hanggita Rachmawati; Susi Lestari; Puspa Ayu Pitayati; Herpandi Herpandi; Indah Widiastuti; Agus Supriadi; Gama Dian Nugroho (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Pulau Semambu village has potential sources of fishery products for the Indralaya area. This program aimed to socialize the manufacture of processed catfish (Clarias batracus) products. This activity is one of the efforts to fulfill nutritional needs and increase family income which is an effort to empower the creative economy through the participation of the Pulau Semambu villagers. Data and information from this service were obtained through observation and interviews. The method has used the PLA (Participatory Learning and Action) method. This service program was attended by 30 Semambu villagers. The product making was easy implemented for Semambu villagers. The post-test score in this activity were 83.36% (fish jerky) and 75.58% (fish bone cracker) regarding the understanding of the product started in definition, making, and advantages. The applicable of product making was a alternative income-generating efforts, in addition to fulfilling nutritional intake.